Physical activity and sedentary behavior across three time-points and associations with social skills in early childhood - Valerie Carson; Eun-Young Lee; Kylie D. Hesketh; Stephen Hunter; Nicholas Kuzik; Madison Predy; Ryan E. Rhodes; Christina M. Rinaldi; John C. Spence; Trina Hinkley (BMC, 2019)
Abstract Background The growth and development that occurs in early childhood has long-term implications, therefore understanding the relevant determinants is needed to inform early prevention and intervention. The objectives of the study were to examine: 1) the longitudinal associations of physical activity and sedentary behavior with social skills and 2) how physical activity and sedentary behavior track over three time-points. Methods Participants were from the Parents' Role in Establishing healthy Physical activity and Sedentary behavior habits (PREPS) project. A total of 251 eligible toddlers and their parents participated at baseline in 2014/15 (time 1; 1.6 ± 0.2 years) and a sub-sample participated at 1-year (time 2; n = 79; 2.7 ± 0.3 years) and 2-year (time 3; n = 77; 3.7 ± 0.4 years) follow-ups. Sedentary time (≤25 counts/15 s), light-intensity physical activity (LPA; 26-419 counts/15 s), and moderate- to vigorous-intensity physical activity (MVPA; ≥420/15 s) were objectively measured with wGT3X-BT ActiGraph accelerometers, and standardized for wear time. Parents reported their children's screen time (television/video, video/computer games) at all three time-points. Parents also reported on children's social skills using the Adaptive Social Behavior Inventory (ASBI) at time-points 2 and 3, and comply (e.g., cooperates; 10 items), express (e.g., joins play; 13 items), and disrupt (e.g., teases; 7 items) subscales were created by summing items. Generalized estimating equations (GEE) were conducted to address objective one. Tracking coefficients (low: β1 < 0.30; moderate: β1 = 0.30-0.59; moderate-high: β1 = 0.60-0.90; high: β1 > 0.9) were conducted using GEE to address objective two. Results Across the study, screen time was negatively associated with express (b = − 0.068, 95%CI: -0.114, − 0.023) and comply (b = − 0.056; 95%CI: -0.094, − 0.018) scores and positively associated with disrupt scores (b = 0.004; 95% CI: 0.001, 0.006). Findings were similar for television/videos but less consistent for video/computer games. No associations were observed for physical activity. Screen time significantly tracked at moderate-high levels (β1 = 0.63; 95% CI: 0.45, 0.81), while all other behaviors tracked at moderate levels (β1 = 0.35-0.49; p < 0.01) over the three time-points. Conclusions Screen time was unfavorably associated with social skills across early childhood. Furthermore, all behaviors tracked at moderate to moderate-high levels from toddler to preschool ages. Therefore, promoting healthy physical activity and sedentary behavior patterns early in life, especially for screen time, may be important.